2020
DOI: 10.18564/jasss.4252
|View full text |Cite
|
Sign up to set email alerts
|

Homophily as a Process Generating Social Networks: Insights from Social Distance Attachment Model

Abstract: Real-world social networks o en exhibit high levels of clustering, positive degree assortativity, short average path lengths (small-world property) and right-skewed but rarely power law degree distributions. On the other hand homophily, defined as the propensity of similar agents to connect to each other, is one of the most fundamental social processes observed in many human and animal societies. In this paper we examine the extent to which homophily is su icient to produce the typical structural properties of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Starting from very general geometric arguments we linked two fundamental relational principles of similarity and complementarity to their characteristic network motifs, that is, triangles and quadrangles correspondingly, and formulated a comprehensive quantitative framework for measuring the extent to which they shape relations in networks. While similarity and its connections to homophily, triadic closure and the density of ego-nets are well-known [31,32,50,57], the principle of complementarity has not been studied systematically from the network perspective. Here we showed that it is linked to the abundance of quadrangles (4-cycles) and the presence of locally dense bipartitelike subgraphs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Starting from very general geometric arguments we linked two fundamental relational principles of similarity and complementarity to their characteristic network motifs, that is, triangles and quadrangles correspondingly, and formulated a comprehensive quantitative framework for measuring the extent to which they shape relations in networks. While similarity and its connections to homophily, triadic closure and the density of ego-nets are well-known [31,32,50,57], the principle of complementarity has not been studied systematically from the network perspective. Here we showed that it is linked to the abundance of quadrangles (4-cycles) and the presence of locally dense bipartitelike subgraphs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the motivating geometric model for similarity-driven relations posits that nodes are positioned in some metric space and the probability of observing a link between them is a decreasing function of the corresponding distance. Such a generic model can be seen as an instance of the class of Random Geometric Graphs (RGGs) [10,50]. The crux is that this very general formulation is enough to guarantee the abundance of triangles (3-cycles), provided that the link probability function decreases with respect to distance at a high enough rate [32].…”
Section: Structural Similaritymentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of research has made ubiquitous the mechanisms known as preferential attachment, triadic closure, and homophily, and has associated them respectively with degree heterogeneity, high clustering, and segregation (see the comprehensive review by Rivera, Soderstrom, and Uzzi (1) as well as other recent publications (2)(3)(4)(5)(6)(7)(8)(9)(10). However, a consensus on how these mechanisms function and interweave seems distant.…”
Section: Introductionmentioning
confidence: 99%